Bioactive Compounds - Biosynthesis, Characterization and Applications [Working Title] 2021
DOI: 10.5772/intechopen.98626
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Spinning and Electro-Spraying as Innovative Approaches in Developing of a Suitable Food Vehicle for Polyphenols-Based Functional Ingredients

Abstract: With recent advances in medical and nutrition sciences, functional foods and nutraceuticals fortified with natural polyphenols have received a lot of attention from both health professionals and the common population in the last few years since their chemical structure allows them to exert various health effects (e.g., antioxidant, anti-inflammatory, immune, antitumor and prebiotic properties). Nonetheless, there are several hurdles to applications of polyphenols in the food system. The most critical hurdle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 153 publications
(251 reference statements)
0
1
0
Order By: Relevance
“…B9 presents associated limitations that must be considered when it is applied. The drawbacks such as low specificity and bioavailability make them suitable compounds to be studied as encapsulated agents [ 16 ]. Evangelho et al reported the high encapsulation of folic acid (in the range of 74.0% and 93.5%) by zein fibers and capsules produced by electrospinning and electrospraying methods, respectively [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…B9 presents associated limitations that must be considered when it is applied. The drawbacks such as low specificity and bioavailability make them suitable compounds to be studied as encapsulated agents [ 16 ]. Evangelho et al reported the high encapsulation of folic acid (in the range of 74.0% and 93.5%) by zein fibers and capsules produced by electrospinning and electrospraying methods, respectively [ 17 ].…”
Section: Introductionmentioning
confidence: 99%